Reconsidering Inheritance Equality: Gender Justice in Religious Court Decisions through the Lens of Maqashid Al-Shariah - Fitriyati, Yusida; Duski Ibrahim; Firman Muntaqo; KN Shofyan Hasan (Nurani: jurnal kajian syari'ah dan masyarakat, 2025)
Traditional Islamic inheritance law stipulates a 2:1 ratio favoring male heirs. However, several decisions issued by Indonesia’s Religious Courts have granted equal shares to male and female children. This shift reflects changing social and economic dynamics, where women increasingly serve as key providers within the family structure. This study aims to analyze and identify judicial reasoning behind the equal distribution of inheritance to sons and daughters, using the maqashid al-shariah framework. Employing a normative-empirical approach, the research integrates case study methods and legal philosophy, drawing on data from court verdicts, interviews, and questionnaires distributed to judges. The data were processed using qualitative descriptive analysis. The findings reveal two main patterns of inheritance division in judicial practice: the traditional model (2:1), aligned with textual sources and the Compilation of Islamic Law, and an equal distribution model (1:1). The 1:1 distribution is not merely the result of mediation, but rather stems from judicial ijtihad that prioritizes substantive justice in light of maqashid al-shariah. Judges’ decisions in favor of equal inheritance are influenced by economic factors (e.g., women as primary earners), social roles (e.g., caregiving responsibilities), mutual agreement among heirs, and a dynamic understanding of maqashid. These rulings highlight the adaptive capacity of Islamic inheritance law to contemporary socio-economic realities without departing from its core principles. This study affirms the significance of context-sensitive ijtihad grounded in public interest (maslahah) for the reformulation of Islamic inheritance law in Indonesia, and emphasizes the judiciary’s progressive role in transforming Islamic family law.